Evaluating Changes in Experimentation, Critical Thinking, and Sense of Wonder in Participants of Science North’s In-School Outreach Programs - Richard, Kaitlin; Pisani, Katrina; Barriault, Chantal L. (Frontiers in Education, 2022)
The aim of this study was to evaluate and report on the impact of an in-school science outreach program on children’s self-reported science knowledge, engagement, and skills through a case study of the Science North in-school outreach program “Mission to Mars.” A logic model method was used to outline the specific inputs, outputs, and measurable outcomes of the program. The program outcomes evaluated in this study were (1) experimentation skills, (2) critical thinking skills, and (3) sense of wonder. Results from pre-post surveys demonstrated that participants had increased program topic knowledge. Students self-reported positive emotions towards science more frequently following exposure to the program. Students’ sense of wonder towards science and towards space also increased post-program. This increase in positive emotion towards science could, in the short term, increase student motivation towards science, which could lead to lasting interests in science in the long term. Only a small number of students reported an increase in experimentation and critical thinking skills post-program. These skills take time to develop, and the single short-term program evaluated in this study may not have given students enough exposure to these skills for them to experience and show a noticeable change. The results of this study can provide informal science institutions like science centers with important insights into the potential learning impact of their in-school outreach programs and can be used to improve current and future programs. Other organizations with in-school science outreach programs can benefit from using the methodology in this study to evaluate their programs, as this research includes a combination of innovative data collection methods such as concept maps to determine what students associate with the word “science,” and the use of an emoji scale to capture student emotions towards science. From a larger perspective, this study evaluating the impacts of in-school science outreach could demonstrate the potential benefits and outcomes of this unique area of informal learning, further solidifying the importance of incorporating these inquiry-based programs into classrooms.